2012
DOI: 10.1029/2012jc008433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of upper‐ocean stratification on tropical cyclone‐induced surface cooling in the Bay of Bengal

Abstract: [1] Surface cooling induced by tropical cyclones (TCs) is about three times larger during premonsoon than during postmonsoon season in the Bay of Bengal. We investigate processes responsible for this seasonal contrast using an ocean general circulation model. The model is forced by TC winds prescribed from an analytic vortex using observed TC tracks and intensities during 1978-2007. The simulation accurately captures the seasonal cycle of salinity, temperature, and barrier layer in this region, with fresher wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
148
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 110 publications
6
148
1
Order By: Relevance
“…Here dT r 5 5 K is used to estimate the raindrop temperature. (Neetu et al 2012). Regions with a weaker salinity stratification in the upper 100 m, such as the Arabian Sea and the northeast Pacific, have smaller SSS response to a cyclone passage (median 5 0.08 psu).…”
Section: Influence Of Tc Rainfall On Sssmentioning
confidence: 99%
See 1 more Smart Citation
“…Here dT r 5 5 K is used to estimate the raindrop temperature. (Neetu et al 2012). Regions with a weaker salinity stratification in the upper 100 m, such as the Arabian Sea and the northeast Pacific, have smaller SSS response to a cyclone passage (median 5 0.08 psu).…”
Section: Influence Of Tc Rainfall On Sssmentioning
confidence: 99%
“…When a barrier layer is present, mixing first has to break through the salinity-stratified layer before it can entrain colder water from below and cool the ocean surface. Neetu et al (2012), for instance, have demonstrated that salinity effects reduce the TC-induced cooling by 30% in the Bay of Bengal during the postmonsoon season (characterized by a very fresh surface layer and the presence of the barrier layer). Consequently, TC intensification rates are significantly higher over regions with barrier layers (Balaguru et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The salinity stratification indeed contributes to maintain a shallow mixed layer in the BoB that is efficiently warmed by surface heat flux and hence the SST remains above 28.5°C (de Boyer Montégut et al 2007), a necessary condition to maintain deep atmospheric convection and rainfall (e.g., Gadgil et al 1984). Similarly, this salinity stratification may also influence the intensity of the tropical cyclones that form over the BoB; the intense salinity stratification in the BoB after the monsoon inhibits vertical mixing and SST cooling below cyclones (Sengupta et al 2008;Neetu et al 2012), promoting an intense evaporation at the ocean surface and hence eventually the intensification of cyclones (e.g., Schade and Emanuel 1999). Last but not least, salinity could act as a marker of changes in the water cycle associated with anthropogenic forcing (e.g., Durack and Wijffels 2010;Terray et al 2012).…”
mentioning
confidence: 99%
“…The BL formation in the BoB is associated with the strong stratification due to the peak discharge from rivers in the post-monsoon season. The intensity of the cyclone largely depends on the degree of stratification (Neetu et al, 2012;Li et al, 2013). The coupled atmosphere-ocean model was found to improve the intensity of cyclonic storms when compared to the uncoupled model over different oceanic regions (Warner et al, 2010;Zambon et al, 2014;Srinivas et al, 2016;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%